EDUCATION ON THE USE OF DIGITAL MEDIA IN DEVELOPING MSME BUSINESSES THROUGH BRANDING IN RIANGGEDE VILLAGE, TABANAN, BALI - Pratiwi, Nuning Indah; Dwi Wahyu Sari, Desak Kade; Indra Satria, Wahyu; Lestara Permana, Gusi Putu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The impact of technological advances and globalization’s influence is strongly felt, especially by MSME players. Designing a branding of MSME products and understanding MSMEs in the use of digital as a medium in branding is one of the techniques in sustainable business development. This service program provides education and training on branding and marketing to utilize digital media through the preparation stage, implementation of activities, and evaluation as the final stage of activities. The desired result of this activity is the creation of product brands to increase and promote MSME products and branding recommendations to create trademarks that can increase citizen awareness of MSME products. As well as the skills and knowledge of MSME managers to carry out branding through the implementation of workshops. So that it can strengthen MSME products, which of course can help business actors expand market share, and introduce and promote products to the public and potential MSME customers in Riang Gede village.